(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article is based on the study of traditional (local) and foreign innovative practices of floriculture development in the territory of Uzbekistan. Appropriate scientific conclusions are given on the basis of the study and comparison of flower beds, their shape and range, design experiments. Suggestions and recommendations for the development of this area have also been developed.